Analysis of scenarios to reduce the probability of acquiring hemolytic uremic syndrome associated with beef consumption - Costa, Magdalena; Brusa, Victoria; Padola, Nora Lía; Etcheverría, Analía Inés; Sampedro, Fernando; Fernandez, Pablo S.; Leotta, Gerardo Anibal; Signorini Porchiett, Marcelo Lisandro (Sage Publications, 2024)
The objective of this study was to develop a quantitative microbial risk assessment (QMRA) model to evaluate potential risk mitigation strategies to reduce the probability of acquiring hemolytic uremic syndrome (HUS) associated with beef consumption in Argentina. Five scenarios were simulated to evaluate the effect of interventions on the probability of acquiring HUS from Shiga toxin-producing Escherichia coli (STEC)-contaminated ground beef and commercial hamburger consumption. These control strategies were chosen based on previous results of the sensitivity analysis of a baseline QMRA model. The application of improvement actions in abattoirs not applying Hazard Analysis and Critical Control Points (HACCP) for STEC would result 7.6 times lower in the probability that consumers acquired HUS from ground beef consumption, while the implementation of improvements in butcher shops would lead to a smaller reduction. In abattoirs applying HACCP for STEC, the risk of acquiring HUS from commercial hamburger consumption was significantly reduced. Treatment with 2% lactic acid, hot water and irradiation reduced 4.5, 3.5 and 93.1 times the risk of HUS, respectively. The most efficient interventions, in terms of case reduction, being those that are applied in the initial stages of the meat chain.